(untitled) (KULT_online, 2018)
In Kneipen, Bars und Clubs. Postmoderne Heimat- und Identitätskontruktionen in der Literatur — the published version of her dissertation, which was written at the Technische Universität Darmstadt — Vanessa Geuen uses an interdisciplinary approach to bring together postmodernity and Heimat. In her analysis of a corpus of Anglo-American and European novels, she argues convincingly that Heimat as a secure and ‘manageable’ place of belonging remains a relevant concept in literary analysis, even if it has lost the immutability that used to characterize it, and that the pubs, bars, and clubs in her corpus fulfill that function.